72. Remdesivir vs Standard Care in Patients with Moderate covid-19. (31st December 2020) - Marty, Francisco M; Malhotra, Prashant; Gottlieb, Robert L; Tashima, Karen T; Galli, Massimo; Chai, Louis Yi Ann; SenGupta, Devi; Hyland, Robert H; Wang, Hongyuan; Zhong, Lijie; Cao, Huyen; Chokkalingam, Anand; et al.
Abstract: Background: Remdesivir (RDV) shortens time to recovery time in patients with severe COVID-19. Its effect in patients with moderate COVID-19 remains unclear. Methods: We conducted an open-label, phase 3 trial (NCT04252664) involving hospitalized patients with confirmed SARS-CoV-2 infection, evidence of pulmonary infiltrates, and oxygen saturation >94% on room air. Patients were randomly assigned 1:1:1 to receive up to 5d or 10d of RDV with standard of care (SoC), or SoC alone; patients could be discharged prior to completing per-protocol assigned treatment duration. RDV was dosed intravenously at 200 mg on d1, 100 mg daily thereafter. Patients were evaluated daily while hospitalized, and via telephone if discharged. The primary endpoint was clinical status on d11 assessed on a 7-point ordinal scale. Results regarding the primary endpoint are expected to be published before IDWeek 2020; we plan to present d28 results at the meeting. Results: In total, 584 patients underwent randomization and started their assigned treatment (191, 5d RDV; 193, 10d RDV; 200, SoC). By d11, ³ 2 point improvement on the ordinal scale occurred in 70% of patients in the 5d arm, 65% in the 10d arm, and 61% in the SoC arm. Patients in the 5d RDV arm were significantly more likely to have an improvement in clinical status than those receiving SoC (odds ratio [OR], 1.65; 95% confidence interval [CI], 1.09–2.48; P=0.017); OR of improvement for the 10d RDV arm compared to SoC was 1.31 (95% CI, 0.88–1.95]; p=0.183). This improvement in the 5-day arm over the SOC arm was noted from d6 through d11. We observed a peak of discharges corresponding with the assigned treatment duration of RDV, with increased discharges at d6 in the 5-day arm and at d11 in the 10-day arm. A worsening of clinical status of ≥ 1 point in the ordinal scale was observed more commonly in the SoC am (n=19, 10%) versus the 5d RDV (n=7, 4%) and 10d RDV (n=9, 5%). Conclusion: RDV for up to 5 days was superior to SoC in improving the clinical status of patients with moderate COVID-19 by d11. We will report d28 outcomes at the meeting. Disclosures: Francisco M. Marty, MD, Allovir (Consultant)Amplyx (Consultant)Ansun (Scientific Research Study Investigator)Avir (Consultant)Cidara (Scientific Research Study Investigator)F2G (Consultant, Scientific Research Study Investigator)Kyorin (Consultant)Merck (Consultant, Grant/Research Support, Scientific Research Study Investigator)New England Journal of Medicine (Other Financial or Material Support, Honorarium for Video)Regeneron (Consultant, Scientific Research Study Investigator)ReViral (Consultant)Scynexis (Scientific Research Study Investigator)Symbio (Consultant)Takeda (Scientific Research Study Investigator)United Medical (Consultant)WHISCON (Scientific Research Study Investigator) Prashant Malhotra, MD, Gilead Sciences Inc. (Scientific Research Study Investigator) Robert L. Gottlieb, MD, Gilead Sciences Inc. (Scientific Research Study Investigator) Karen T. Tashima, MD, Bristol-Myers Squibb (Research Grant or Support)Gilead Sciences Inc. (Grant/Research Support, Scientific Research Study Investigator)GlaxoSmithKline (Research Grant or Support)Merck (Research Grant or Support)Tibotec (Research Grant or Support)Viiv Healthcare (Research Grant or Support) Massimo Galli, MD, Gilead Sciences Inc. (Grant/Research Support, Scientific Research Study Investigator, Advisor or Review Panel member, Other Financial or Material Support, Personal fees) Louis Yi Ann Chai, MD, Gilead Sciences Inc. (Scientific Research Study Investigator) Devi SenGupta, MD, Gilead Sciences Inc. (Employee, Shareholder) Robert H. Hyland, MD, Gilead Sciences Inc. (Employee, Shareholder) Hongyuan Wang, PhD, Gilead Sciences Inc. (Employee, Shareholder) Lijie Zhong, PhD, Gilead Sciences Inc. (Employee, Shareholder) Huyen Cao, MD, Gilead Sciences Inc. (Employee, Shareholder) Anand Chokkalingam, PhD, Gilead Sciences (Employee) Anu Osinusi, MD, Gilead Sciences (Employee) Diana M. Brainard, MD, Gilead Sciences (Employee) Michael Brown, MD, Gilead Sciences Inc. (Scientific Research Study Investigator) Ane Josune Goikoetxea, MD, Gilead Sciences Inc. (Scientific Research Study Investigator) Mamta Jain, MD, Gilead Sciences Inc. (Scientific Research Study Investigator, Research Grant or Support)GlaxoSmithKline (Advisor or Review Panel member)Janssen (Research Grant or Support)Merck (Research Grant or Support) David Shu Cheong Hui, MD, Gilead Sciences Inc. (Scientific Research Study Investigator) Enos Bernasconi, MD, Gilead Sciences Inc. (Scientific Research Study Investigator) Christoph Spinner, MD, AbbVie (Advisor or Review Panel member, Other Financial or Material Support, Travel)Bristol-Myers Squibb (Grant/Research Support, Advisor or Review Panel member, Other Financial or Material Support, Travel)Gilead Sciences Inc. (Grant/Research Support, Scientific Research Study Investigator, Advisor or Review Panel member, Other Financial or Material Support, Travel)Janssen (Grant/Research Support, Advisor or Review Panel member, Other Financial or Material Support, Travel)MSD (Grant/Research Support, Advisor or Review Panel member, Other Financial or Material Support, Travel)Viiv Healthcare (Grant/Research Support, Advisor or Review Panel member, Other Financial or Material Support, Travel)